Jamaica’s Trade Facilitation Task Force : Involving Public and Private Sectors to Improve Competitiveness - Tomlinson, Kanika Y. (International Finance Corporation, Washington, DC, 2017)
Jamaica is taking steps to strengthen its trade environment as a way to improve the ease and ways of doing business and stimulate growth. In February 2015, Jamaica formed its National Committee on Trade Facilitation, known as the Trade Facilitation Task Force (TF2). During its first year, theTask Force had fruitful consultations with its members in the public and private sectors on how to increase trade facilitation in Jamaica. These consultations laid the foundation for the creation of a Trade Facilitation Project Plan, currently in use as a guide for the execution and monitoringof Jamaica’s trade-competitiveness activities. This SmartLesson describes the establishment of the Task Force and the progress of the Project Plan— and shares key lessons learned along the way.